Anthracnose of soybean: Occurrence, epidemiology and management approaches: ANTHRACNOSE OF SOYBEAN: OCCURRENCE, EPIDEMIOLOGY AND MANAGEMENT APPROACHES - MANOJ KUMAR YADAV,; CHANDRAKANT SINGH,; DASARI SREEKANTH,; ADITYA KUMAR,; SUJIT KUMAR YADAV,; SANJEEV KUMAR,; P DURAIMURUGAN,; ARCHANA ANOKHE,; ARJUN LAL YADAV, (Journal of Oilseeds Research, 2025)
Colletotrichum truncatum is the primary causal agent of anthracnose disease, which has been identified as a significant global soybean production obstacle, especially in warm and humid environmental conditions. The disease isseed-borne in nature exerting a major effect on yield and quality of seeds, and spreading quickly via wind and rain splash. The current understanding of the epidemiological studies, the anthracnose disease cycle and its management is discussed. It has been reported that cultural techniques such crop rotation, disease free seed, residue management, and optimal planting density minimize primary inoculum and limit the spread of the disease. Although, host resistance is frequently partial because of significant pathogenic diversity, it offers an environmentally sustainable foundation for disease management. It has been found that, chemical management through seed treatment and tailored foliar fungicide applications at key growth stages efficiently suppresses disease development. Additionally, the most effective method for long-term prevention of disease and yield protection is through using integrated disease management methods, which incorporate cultural techniques, resistant cultivars, timely disease tracking, and need-based fungicide application. In order to improve long-term management of soybean anthracnose, future plans place a strong emphasis on developments in molecular breeding, pathogen population analysis, environmentally conscious management options, and precision agricultural techniques. Overall, this review underscores the importance of comprehensive and integrated strategies for mitigating anthracnose and assuring sustained soybean production.